2014
DOI: 10.1089/met.2013.0153
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Body Mass Index and Prenatal Fasting Glucose Are Effective Predictors of Early Postpartum Metabolic Syndrome in Spanish Mothers with Gestational Diabetes

Abstract: Women having GDM are at threat of early postpartum metabolic syndrome. This risk can be easily identified by assessing prepregnancy BMI and antenatal fasting glycemia in the first pregnancy visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…13 TG, TC and LDL concentrations were higher in the HDP/GDM group in the first trimester as shown above. These findings suggested that lipids in early gestational age show a more maternal metabolic condition than the physiological requirement for fetal growth.…”
Section: Discussionsupporting
confidence: 66%
“…13 TG, TC and LDL concentrations were higher in the HDP/GDM group in the first trimester as shown above. These findings suggested that lipids in early gestational age show a more maternal metabolic condition than the physiological requirement for fetal growth.…”
Section: Discussionsupporting
confidence: 66%
“…Unlike our results, other studies showed an association between pre-gestational BMI indicative of overweight and obesity and the presence of MS in the postpartum period. 9,16,18 In these studies, however, MS was diagnosed in the postpartum period in women with a diagnosis of GDM who, according to the pre-gestational BMI, were overweight/obese and whose levels of fasting glucose were high. 9,16,18 In relation to the biochemical analysis, only the levels of HDL-c in the 16th week and the triglyceride levels in the postpartum period remained significantly associated with MS in this study.…”
Section: Discussionmentioning
confidence: 99%
“…9,16,18 In these studies, however, MS was diagnosed in the postpartum period in women with a diagnosis of GDM who, according to the pre-gestational BMI, were overweight/obese and whose levels of fasting glucose were high. 9,16,18 In relation to the biochemical analysis, only the levels of HDL-c in the 16th week and the triglyceride levels in the postpartum period remained significantly associated with MS in this study. Corroborating these findings, a study carried out at the beginning of the gestation showed higher average levels of triglycerides (192.5±87.5 mg/dl and 105±61.2 mg/dl) and lower HDL-c (456.79±114.2 mg/ dl and 532.92±152.26 mg/dl) in women with MS in comparison to those without it.…”
Section: Discussionmentioning
confidence: 99%
“…In South India, the reported incidence of postpartum DM among women with history of previous GDM is even higher within the first five years with over 90% being affected within 10 years of delivery [5]. After delivery, women with GDM often have an increased risk of developing metabolic syndrome, which is also seen in South Asian women [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%